KOMUNIKASI INTERPERSONAL DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA - Usman, Usman; Qorilani, Rezki; Anto, La Ode; Binsar Kristian, Feliks Anggia (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine the causal relationships among interpersonal communication, leadership, work motivation, and employee performance at Bank Sultra in Muna Regency. Using a census approach, all 32 employees were included as research respondents. Data were analyzed using Path Analysis in SmartPLS to evaluate both direct and indirect effects among variables. The findings indicate that interpersonal communication has a positive and significant effect on work motivation, while leadership demonstrates a powerful and significant influence on motivation. However, interpersonal communication does not have a significant direct impact on employee performance. In contrast, leadership has a positive and significant effect on performance. Work motivation also exerts a powerful, significant influence on employee performance. Furthermore, the indirect effect of interpersonal communication on performance via motivation is not statistically significant, whereas leadership indirectly enhances performance by increasing motivation.